Brief Report: Recent HIV Infection Surveillance in Routine HIV Testing in Nairobi, Kenya: A Feasibility Study - Welty, Susie; Motoku, John; Muriithi, Chris; Rice, Brian; de Wit, Mariken; Ashanda, Brenda; Waruiru, Wanjiru; Mirjahangir, Joy; Kingwara, Leonard; Bauer, Richard; Njoroge, David; Karimi, Jesse; et al. (Journal of acquired immune deficiency syndromes (1999), 2020)
Serological tests can distinguish recent (in the prior 12 months) from long-term HIV infection. Integrating recency testing into routine HIV testing services (HTS) can provide important information on transmission clusters and prioritize clients for partner testing. This study assessed the feasibility and use of integrating HIV recency into routine testing. We conducted a multi-method study at 14 facilities in Kenya, and key informant interviews with health care providers. We abstracted clinical record data, collected specimens, tested specimens for recent infection, returned results to participants, and conducted a follow-up survey for those recently infected. From March to October 2018, we enrolled 532 clients who were diagnosed HIV-positive for the first time. Of these, 46 (8.6%) were recently infected. Women aged 15-24 years had 2.9 (95% confidence interval: 1.46 to 5.78) times higher adjusted odds of recent infection compared with 15-24-year-old men and those tested within the past 12 months having 2.55 (95% confidence interval: 0.38 to 4.70) times higher adjusted odds compared with those tested ≥12 months previously. Fourteen of 17 providers interviewed found the integration of recency testing into routine HTS services acceptable and feasible. Among clients who completed the follow-up interview, most (92%) felt that the recency results were useful. Integrating recent infection testing into routine HTS services in Kenya is feasible and largely acceptable to clients and providers. More studies should be done on possible physical and social harms related to returning results, and the best uses of the recent infection data at an individual and population level.